2017
DOI: 10.1155/2017/1501038
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a HPLC‐UV Method for the Evaluation of Ellagic Acid in Liquid Extracts of Eugenia uniflora L. (Myrtaceae) Leaves and Its Ultrasound‐Assisted Extraction Optimization

Abstract: A simple HPLC-UV method has been developed and validated for the quantification of ellagic acid (EA) in ethanol extracts of Eugenia uniflora L. (Myrtaceae) leaves. The ultrasound-assisted extraction (UAE) optimization was performed using a Box Behnken design (33) combined with response surface methodology to study the effects of the ethanol concentration (%, w/w), extraction time (minutes), and temperature (°C) on the EA concentration. The optimized results showed that the highest extraction yield of EA by UAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Thus, the LOD/LOQ values for this method were approximately 17 fold higher than those of our simultaneous determination method, suggesting that our method can be used more effectively to detect and quantify small amounts of quercetin 3-glucuronide. In addition, Assunção, Conceição, Borges, et al [30] reported a validated method for which the LOD/LOQ values for ellagic acid were 0.66/2.22 μg/mL values that are similar to those we measured for the present method.…”
Section: Limit Of Determination and Limit Of Quantificationsupporting
confidence: 87%
“…Thus, the LOD/LOQ values for this method were approximately 17 fold higher than those of our simultaneous determination method, suggesting that our method can be used more effectively to detect and quantify small amounts of quercetin 3-glucuronide. In addition, Assunção, Conceição, Borges, et al [30] reported a validated method for which the LOD/LOQ values for ellagic acid were 0.66/2.22 μg/mL values that are similar to those we measured for the present method.…”
Section: Limit Of Determination and Limit Of Quantificationsupporting
confidence: 87%
“…Detection was achieved on the BDD electrode vs. Ag/AgCl. ( Table 2), and also lower than previously reported LC-UV methods [23][24][25]. Intra-day and inter-day precision were in the range of 0.23-0.47 % and 0.64-1.02 % RSD, respectively.…”
Section: Analytical Performance For Analysis Of Gallic and Ellagic Acmentioning
confidence: 49%
“…The RSD value between the data of two different days was 2.58%. The quantification procedure was precise, as indicated by the low RSD value (less than 5%) recommended by ANVISA [25]. The recovery value of nimbolide was 101.87% and RSD was 1.84%, which indicated that the quantification method had sufficient accuracy.…”
Section: Hplc Quantification Methods Validationmentioning
confidence: 89%
“…For the MAE single factor experiment, one factor was varied in a certain range while all other factors were kept constant. The extraction parameters were solid/liquid ratio (1:10, 1:20, 1:30, 1:40, and 1:50 g/mL), microwave power (210, 280, 350, 420, and 490 W), and extraction time (10,15,20,25, and 30 min). The nimbolide content was expressed as mean ± standard deviation (SD) for three replicates.…”
Section: Screening Of Single Variablesmentioning
confidence: 99%